Educational Relationship in University Tutoring: Compre-hensive Study from the Teaching Perspective : Relación educativa en la tutoría universitaria: estudio comprensivo desde la perspectiva docente (Papeles, 2023)
Introduction: University tutoring generates a space for communication between students and teachers and personal, academic and professional support. Teaching during the pandemic has inexorably incorporated the use of technology in the educational relationship. This study delves into the teaching perspective in the planning of the tutorial action and analyzes the relationship that is promoted. Methodology: Two qualitative discussion groups are developed with 11 university professors and a restitution to the field session. Results and conclusion: The results highlight a generational gap in the use of technology and in the means for the construction of learning. In addition, four categories of analysis emerge: communication, from the collaborative dimension and its limits; personalization, from everyday life and the personal narratives of students; the promotion of academic skills and asymmetry in the educational relationship. Conclusions: The study discusses the potential of balancing synchronous and asynchronous spaces to plan tutoring that considers the needs of the student at different times, attending to the promotion of autonomy and learning by peers and the care to accompany from personal identity and self-knowledge.
Keywords: university tutoring; educational relationship; generational gap; professional qualities; empathy